Comparative plastome assembly of the yellow ironweed (Verbesina alternifolia) using Nanopore and Illumina reads - Tomasello, Salvatore; Manzo, Eleonora; Karbstein, Kevin (Frontiers in Plant Science, 2024)
Chloroplast genomes (plastomes) represent a very important source of valuable information for phylogenetic and biogeographic reconstructions. The last decade has registered a proliferation of such studies and more than 40,000 plastomes are to date available in public repositories. The use of short reads (as those produced from Illumina sequencing), along with de-novo read assembly, has been considered the "gold standard" for plastome reconstruction. However, short reads often cannot reconstruct long repetitive regions in chloroplast genomes. Long Nanopore (ONT) reads can help bridging long repetitive regions but are by far more error-prone than those produced by Illumina sequencing.Verbesina is the largest genus of tribe Heliantheae (Asteraceae) and includes species of economic importance as ornamental or as invasive weeds. However, no complete chloroplast genomes have been published yet for the genus. We utilized Illumina and Nanopore sequencing data and different assembly strategies to reconstruct the plastome of Verbesina alternifolia and evaluated the usefulness of the Nanopore assemblies. Our study highlights the usefulness of the Nanopore technology for assembling rapidly and costeffectively chloroplast genomes, especially in taxonomic groups with paucity of publicly available plastomes.